ANALYSIS OF THE INFLUENCE OF SHARIA BANKING LITERACY AND SERVICE QUALITY ON BECOME DECISIONS SHARIA BANK CUSTOMERS - Rahma Hayati; Gusnia Rahayu; Kubota Tariq (Journal Of Sharia Banking, 2023)
This research was conducted at the Darul Al-Ikhlas Modern Islamic Boarding School and the sample of this study was educational staff. The background of the problem in this study is based on the theory of Islamic banking literacy increases, the decision to become a customer will also increase and the quality of service increases, the decision to become a customer will also increase. But the phenomenon in the field in this study is a pesantren-based school but there are still educational staff who still use conventional banks. The theory used in this study is the theory of Islamic banking literacy, service quality and decision making to become a customer of Islamic banks. The theory discussed by researchers is related to the field of Islamic banking and consumer behavior. This theoretical approach is also related to the problem under study, namely Islamic banking literacy, service quality and the decision to become an Islamic bank customer in Darul Al-Ikhlas Islamic boarding school education staff and other theoretical supporters. This type of research used is quantitative research. The samples used in this study were 41 samples with saturated sample technique. Data analysis techniques used validity test, reliability test, normality test, classic assumption test namely multicollinearity test, heteroscedasticity test, and autocorrelation test while hypothesis testing included t test and F test, R2 determination coefficient test and multiple linear regression analysis. The results of this study indicate that Islamic banking literacy has a positive effect on the decision of educational staff to become Islamic bank customers at the Darul Al-Ikhlas modern Islamic boarding school. Service quality has a positive effect on the decision of educational staff to become customers of Islamic banks at the Darul Al-Ikhlas Islamic boarding school. Simultaneously, Islamic banking literacy and service quality influence the decision to become a customer of an Islamic bank. .